Penerapan Ekonomi Kerakyatan Pada Sistem Akad Gadai Perspektif al-Qur’an - Imam Hanafi (STIU Al-Mujtama Pamekasan, 2022)
Lack of public awareness of the importance of social economy both in a broad scope and in a small scope, namely in society is a real problem for a country. Because the small and medium-sized business sector is a milestone for basic-level business actors. This causes the lack of community economic actors, as evidenced by the increasing number of rural communities and/or people with a low economy leaving their activities such as farming, trading and small fishermen. They prefer to do instant business such as wandering and playing stocks and sometimes exceeding the limit by violating Islamic law. Thus, the application of populist economics in the pawn contract system based on the Qur'an with thematic studies, as a solution to overcome the economic problems of the people who are spared from the practice of usury. Keywords: economy, populist, pawn, al-Qur'an